Peran pokdarwis dewi arum pulosari dalam peningkatan ekonomi masyarakat desa wisata pandean berbasis bisnis kreatif - Maharani, Tri Sakti; Hidayati, Amalia Nuril; Habib, Muhammad Alhada Fuadilah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to determine the role of local human resources who are members of the tourism awareness group in the management of Pandean Tourism Village so that it advances and develops as it is today. This study uses a qualitative descriptive method with the technique of making informants using purposive. Data collection techniques used are interviews and field observations. The results of this study indicate that the role of Pokdarwis Dewi Arum Pulosari is in advancing village tourism in its own way and introducing local culture to the community through optimizing social media, improving the community's economy and providing additional hospitality knowledge to the surrounding community in managing the Pandean tourist village. The strategy carried out by Pokdarwis Dewi Arum Pulosari in improving the welfare of the community is to provide soft skill training in tourism village management and increase community creativity through socialization and direct examples so that creative communities participate in developing natural tourism in Pandean Village and improve the local community's economy by providing opportunities creative businesses such as tour guides to transportation service providers. The supporting factors for tourist villages are the willingness of the community to actively participate, the advancement of community innovation, beautiful natural resources, and high solidarity among the community to advance the village